If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 2 = 19x + -7 Reorder the terms: 2 + 16x = 19x + -7 Reorder the terms: 2 + 16x = -7 + 19x Solving 2 + 16x = -7 + 19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19x' to each side of the equation. 2 + 16x + -19x = -7 + 19x + -19x Combine like terms: 16x + -19x = -3x 2 + -3x = -7 + 19x + -19x Combine like terms: 19x + -19x = 0 2 + -3x = -7 + 0 2 + -3x = -7 Add '-2' to each side of the equation. 2 + -2 + -3x = -7 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = -7 + -2 -3x = -7 + -2 Combine like terms: -7 + -2 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 3+4=2.4 | | 4(x^2-2)=0 | | 3x-9=4-3x | | p=6-3/4q | | 8(4x-7)-(x-3)=7(x+7)+5 | | 7=a+3 | | x^2+8x=2x | | =10+7q-3r+2q-r | | 5(-3)+2=4(2y+5) | | 12+5x=19+2x | | Sin*4x+sin*6x=0 | | 4(x+6)=10x-36 | | z/8-1=9 | | x^2+100x=24 | | (-15m+2)(15-2)=0 | | 8h-11=16 | | 1/x-1/(x-5)=9/100 | | 12(x-4)=9 | | (y-8)(y+8)=63 | | -2n-12p= | | -2n+22=4p | | 4(x-2)=3(x+10) | | 7=10e-4f | | -1/2x2-3 | | 7-5e=4f-34 | | 7-5e=rf-34 | | 3y-5y=5y+1 | | -3r+6u+10r-9u= | | 9m-8t=56 | | 5m+8t=0 | | 27b-18=3b-9 | | 7g+4h=54 |